Applying the Elaboration Likelihood Model to increase recall of conservation messages and elaboration by zoo visitors. Issue 6 (2nd June 2016) - MacDonald, Edith; Milfont, Taciano; Gavin, Michael
Abstract : Zoos aspire to facilitate sustainable behaviours in visitors and conservation messages are plentiful in zoos. However, the degree to which these messages are being received and processed by visitors on site has rarely been studied. In our paper, we studied the effectiveness, as measured in message recall, of a common mode of face-to-face communication used in zoos, animal talks. We compared animal talks based on a theoretical framework, the Elaboration Likelihood Model (ELM), to a control group in which no framework was used. A two-phase ELM-based training programme, which instructed staff in techniques to increase cognitive possessing in visitors, led to increased visitor satisfaction after one training programme and increased relevancy (connected to the visitor's life) and elaboration (provoked thinking) after a second training session. There was a small number of staff who did not integrate conservation messages into talks despite repetitive training. Implications for zoos and their goal of effectively communicating conservation messages to visitors are discussed.